ХАРАКТЕРИСТИКА БАКТЕРИОСКОПИЧЕСКОГО ИССЛЕДОВАНИЯ ПРИ ЛОКАЛЬНО ГНОЙНЫХ ИНФЕКЦИЯХ У НОВОРОЖДЕННЫХ ДЕТЕЙ - Турсунбаева, Феруза Фазиловна; Гулямова, Муяссар Абдусаттаровна; Ходжиметов, Хасан Аббасович; Яхёева, Зиёда Бердиназаровна (FORCIPE, 2022)